An Animal Model (Guinea Pig) of Ocular Siderosis: Histopathology, Pharmacology, and Electrophysiology. (March 2015) - Mumcuoglu, Tarkan; Ozge, Gokhan; Soykut, Bugra; Erdem, Onur; Gunal, Armagan; Acikel, Cengizhan
Abstract Purpose: Ocular siderosis is a rare sight-threatening complication that occurs after a penetrating ocular injury by an iron-containing foreign body. The purposes of this study were to (i) investigate the histopathology, electrophysiology and iron levels/accumulation in ocular siderosis using an animal (Guinea pig) model and (ii) determine the appropriate timing for follow-up foreign body-removal surgery. Materials and methods: Thirty guinea pigs were divided into five groups (n = 6 animals/group). On day-1, an iron body was inserted into the vitreous of the right eye of all animals; the left eyes were left undisturbed and were used as controls. At the end of each week during the 5-week study period, electroretinography (ERG) was performed on all animals in one of the five groups. Each animal in that group was sacrificed, after which both eyes were enucleated for histopathological and pharmacological evaluation of intraocular iron. Results: Accumulated iron levels of study eyes were significantly higher than those of control eyes (135.13 and 13.55 μg/g, respectively, p < 0.01). In addition, there was a significant decrease in electrophysiological responses of study eyes. During the first week, iron levels were higher in study eyes than control eyes, but neither histological iron accumulation nor decreased electrophysiological responses could be detected. By the end of the second week, increased iron accumulation was observed histologically in intraocular tissues, along with signs of retinal toxicity, as verified by decreased electrophysiological responses. Conclusions: The present study indicates that the 14th day after a penetrating eye injury by an iron-containing intraocular foreign body represents a clinically critical threshold, after which structural damage to and functional alterations in ocular tissues occur.